Is the privacy of information protected in a neonatal intensive care unit? : an observational study - Porta, Roser (Array, 2019)
Respecting patients’ intimacy and confidentiality can be a challenge in the neonatal intensive care units (NICUs) designed according to traditional standards (e.g. a single big room with a number of cots and incubators located close one to another). Concerned about this topic, two members of the team designed a study to check the quality of the confidentiality in the NICU area, and identify opportunities for improvement. This is an observational study performed for a period of one month. The observed team was not aware of being observed. During observation time, a total of 147 hours, 25 confidentiality violation situations were encountered. Twelve (48%) were comments, spoken with a loud voice, about the patients in the NICU area or in adjacent areas, 24% (6/25) were related to the privacy issues due to leaving medical documentation or computer screens available for anybody to see or informing parents in a way that could be heard by parents of other babies, 12% (3/25) were phone conversations about patients in a loud voice, 4% (1/25) were answering questions to parents or relatives about other babies. The medical and personal information of the patients in the NICU is often exposed and shared with parents of other patients and non-related professionals. The architectural design of the traditional NICUs, some socio-cultural issues in South European countries, and the difficulties in changing attitudes are the critical points to focus on to start a quality educational project to protect the right to intimacy and confidentiality of vulnerable children and parents admitted to the NICUs.